Study of Compressibility and Atomic Radius of Lead Sulfide (PBS) - Adhikari, D. R.; Adhikari, S. K.; Baral, S. P. (Journal of Lumbini Engineering College, 2024)
The purpose of the paper is to study the relationship between temperature and various physical properties of Lead Sulfide (PbS) such as atomic radius, nanopar ticle size, compressibility, energy band gap, and density. It is noted that PbS has a narrow band gap at low temperatures and acts as a semiconductor. The atomic radius is found to be linearly dependent on temperature. The size of the nanopar ticle is influenced by the energy band gap and the effective mass of electrons and holes in the material. The unique properties of PbS have various applications in the fields of optoelectronics, thermo-electronics, and nanotechnology. We have used various parameters to calculate the atomic radius, bulk modulus, nanopar ticle size, and compressibility, which play an important role in recent technologies and devices. The results are in good consistent with experimental data.